Building brains that communicate like machines. (10th November 2017) - Graham, Daniel
Abstract: Reverse engineering human cognitive processes may improve artificial intelligence, but this approach implies we have little to learn regarding brains from human-engineered systems. On the contrary, engineered technologies of dynamic network communication have many features that highlight analogous, poorly understood, or ignored aspects of brain and cognitive function, and mechanisms fundamental to these technologies can be usefully investigated in brains.